Penerapan Model Pembelajaran Picture and Picture Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPS Kelas V Sekolah Dasar - Risal M. Merentek; Giebrilien Giebrilien; Brianne E. J. Komedien; Fransiska R. Korompis; Juliana K. Tagupia (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the social studies learning outcomes of fifth grade students at Sarongsong State Elementary School by applying the Picture and Picture learning model. This type of research is classroom action research which includes two action cycles and goes through 4 stages which include: (1) Planning, (2) Implementation, (3) Observation and (4) Reflection. In the implementation of the actions of cycle I and cycle II which also experienced an increase even though the implementation time was not that far away, due to the willingness to learn and the competence of a teacher who was so great as to be able to change the situation which in cycle I was considered unsuccessful but in cycle II experienced a very good increase. In the first cycle the average student score was 66.33% while the KKM classically was >75 and in the second cycle it experienced growth and the student's average score was at 92.22% and had passed the minimum completeness criteria for the subject. Thus the results of research at SD Negeri Sarongsong have been well achieved